2002
DOI: 10.1253/circj.66.993
|View full text |Cite
|
Sign up to set email alerts
|

Candesartan Cilexetil Improves Left Ventricular Function, Left Ventricular Hypertrophy, and Endothelial Function in Patients With Hypertensive Heart Disease.

Abstract: atients with hypertension often develop left ventricular (LV) hypertrophy as a physical response to chronic pressure overload, and it can result in decreased chamber compliance and eventually lead to the deterioration of LV systolic function. Any of these changes contribute to the development of heart failure. Angiotensin II is now believed to play a critical role in the pathogenesis of hypertrophy and/or hyperplasia of vascular smooth muscle cells, 1-6 and angiotensin II receptor blockers (ARBs) are a new cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“…7 An acute functional change in vascular smooth muscle relaxation, improvement in endothelial dysfunction, decrease in arterial wall thickness, decrease in collagen content and reversal of smooth muscle cell hypertrophy have been proposed as mechanisms of the improvement in PWV by ARB. [21][22][23] However, it is unlikely that treatment with ARB for only 4 weeks would improve the structure of the vasculature. Short-term treatment of ARB may improve PWV mainly through functional mechanisms such as vascular smooth muscle relaxation and improvement in endothelial dysfunction, because BP was also decreased after ARB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…7 An acute functional change in vascular smooth muscle relaxation, improvement in endothelial dysfunction, decrease in arterial wall thickness, decrease in collagen content and reversal of smooth muscle cell hypertrophy have been proposed as mechanisms of the improvement in PWV by ARB. [21][22][23] However, it is unlikely that treatment with ARB for only 4 weeks would improve the structure of the vasculature. Short-term treatment of ARB may improve PWV mainly through functional mechanisms such as vascular smooth muscle relaxation and improvement in endothelial dysfunction, because BP was also decreased after ARB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ACEI and ARB are reportedly hypotensive agents that have a preventive effect on myocardial remodeling, anti-inflammatory actions and improve that function of the vascular endothelial cells. 26,27 However, these actions have not yet been fully elucidated. Therefore, we evaluated the changes in the renin -angiotensin system that were antagonistic to ANP by treating rats with drugs that block the reninangiotensin system in order to elucidate the relationship between ANP and the renin -angiotensin system in NO inhibitor-induced hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Previous studies have shown LVH to be related to an impaired EDV in hypertensive subjects. [7][8][9][10][11][12][13][14] However, the relationship between EDV and LVMI has not been investigated in a general population. Furthermore, as the degree of EDV in peripheral conductance arteries and resistance arteries are not closely related, [15][16][17] there is a need to clarify the relationship between EDV in these two types of arteries and LVMI in the same individuals.…”
Section: Introductionmentioning
confidence: 99%